A review of transit accessibility models: Challenges in developing transit accessibility models. Issue 10 (3rd August 2020) - Malekzadeh, Ali; Chung, Edward
Abstract: The increasing traffic congestion and pollution in cities is seriously threatening the livability and development of urban areas. As a result, the growing importance of transit accessibility is attracting considerable attention among researchers in transport planning, urban geography and sustainable development. To help solve these increasingly serious issues, public transport studies related to transit network design, transit system evaluation, land use, and transport planning in cities require accurate transit accessibility measurements. The past three decades have seen a burgeoning body of research on transit accessibility, and numerous models have been developed to measure transit accessibility for different purposes. This comprehensive review explores the existing transit accessibility models and highlights their practical advantages and drawbacks from different perspectives to help researchers and transport planners employ the most suitable models to counter mounting traffic threats. Accordingly, this review seeks to answer the following questions. What are the major challenges in developing transit accessibility models? What are the potential research directions to address these challenges? Why have different researchers developed different models for measuring transit accessibility in cities? How important is it to estimate travel impedance or attractiveness of opportunities accurately? Finally, what are the important criteria for developing future transit accessibility models? To deliver its outcomes and answer these questions, this paper reviews transit accessibility models under three main categories: system accessibility, system-facilitated accessibility and access to destinations.